2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610427
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic anomalous filtering in Diffusion-Weighted Magnetic Resonance Imaging

Abstract: Noise is inherent to Diffusion-Weighted Magnetic Resonance Imaging (DWI) and noise reduction methods are necessary. Although process based on classical diffusion is one of the most used approaches for digital image, anomalous diffusion has the potential for image enhancement and it has not been tested for DWI noise reduction. This study evaluates Anomalous Diffusion (AD) filter as DWI enhancement method. The proposed method was applied to magnetic resonance diffusion weighted images (DW-MRI) with different noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the literature research is found that supports the anomalous behavior in the MRI signal decay [9] and other anomalous highlights involved to brain images [10]. Furthermore, the AAD filter demonstrates potential to enhance MRI diffusion weighted image quality [8], and this applicability is hereby extended to relaxometry images.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In the literature research is found that supports the anomalous behavior in the MRI signal decay [9] and other anomalous highlights involved to brain images [10]. Furthermore, the AAD filter demonstrates potential to enhance MRI diffusion weighted image quality [8], and this applicability is hereby extended to relaxometry images.…”
Section: Introductionmentioning
confidence: 73%
“…1 in several biomedical image techniques. However, in recent studies it has been shown that AAD filtering (resulting by porous media equation [7]) has a better filtering performance than the classical diffusion approach when it is applied to MRI brain imaging [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation